Instrumental Competence Development of Internship Students in English Translation and Interpreting Department - Hüsna Ekşioğlu (Skad)
This study explores the development of instrumental competence among students of the English Translation and Interpreting Department at Sakarya University during their internships. Instrumental competence, defined as the ability to effectively use technological tools in translation processes, plays a crucial role in modern translation education. The research specifically examines how fourth-year students' proficiency in Computer-Assisted Translation (CAT) tools, machine translation systems, and digital resources evolves throughout their mandatory internships. Additionally, the study assesses students' perceptions of their academic preparation and how well university courses equip them to meet the technological demands of the translation industry. Using a qualitative research design, semi-structured interviews were conducted with 15 students who completed internships in translation companies. The findings highlight that internships significantly enhance students' instrumental competence, particularly in using CAT tools and other digital resources. However, gaps were identified in the curriculum, particularly in offering practical experiences with advanced translation technologies. Recommendations are provided for improving translation education to better bridge the gap between academic learning and professional technological requirements. The study underscores the importance of internships in advancing instrumental competence, suggesting that hands-on experience with industry-standard tools is essential for students' success in the field, ensuring they are adequately prepared for real-world challenges.